Correlation Between Anti-Topoisomerase I and C-Reactive Protein Antibody Level with Modified Rodnan Skin Score On Systemic Sceloris Patients - Dr. dr Sumartini Dewi, SpPD, K-R; Wisynu Tresnadi A.B; Rachmat Gunadi Wachjudi (Indonesia Rheumatology Association, 2021)
A B S T R A C T Systemic sclerosis is characterized by extensive and progressive organ fibrosis processes leading to organ failure and death. Modified Rodnan Skin Score (mRSS) had been used as a clinical parameter of skin fibrosis. Anti- topoisomerase I and C-Reactive Protein (CRP) are potential biomarkers for assessing disease activity. The study was performed to determine the association of anti-topoisomerase I and CRP antibodies with mRSS values. We performed an observational analytic study based on primary and secondary data. Systemic sclerosis patient sera data was obtained from Dewi S et al's study, taken from May 2015 to June 2017. Serum Anti - topoisomerase I antibody and CRP level analysis were performed in December 2017. Fifty six samples analyzed. Fifty four subjects (96.4%) out of 56 subjects are women with an average age of 37 ± 11 years, 41 subjects (73.3%) has disease duration over 2 years, 34 subjects (60.7%) has difuse systemic sclerosis, 41 subjects (73.3%) in steroid therapy and 50 subjects (89.3%) in methotrexate therapy. The statistical analysis showed no correlation between anti-topoisomerase I antibody and CRP levels with mRSS values (r = 0.205, p = 0.064; r = -0.134, p = 0.167), but there was a positive correlation of anti-topoisomerase I antibody level with mRSS (r = 0,422 p = 0,007) and negative correlation between CRP level and mRSS (r = -0,511 p = 0,001) in diffuse sclerosis systemic. From this study we concluded that anti-topoisomerase I antibody and CRP level were not correlated with mRSS, but in patient with diffuse systemic sclerosis there was a positive correlation of anti-topoisomerase I antibody level with mRSS and negative correlation between CRP level and mRSS.